TRADISI PARADIGMA INDUKTIF DALAM KAJIAN KEILMUAN ISLAM - Ahmad Fuad Hasyim (Wahana Islamika: Jurnal Studi Keislaman, 2019)
The scientific tradition in Islam recognizes two paradigms, namely the deductive paradigm and the deductive paradigm. In its journey, the deductive paradigm is more developed than the inductive paradigm. As a result, science based on inductive paradigms such as astronomy and medicine does not develop. Therefore this paper seeks to reveal the scientific tradition in Islam which relies on an inductive paradigm. This research is a qualitative research with a library research style. The results of the study show that the inductive tradition in Islamic scientific studies is still being used from classical times to modern times with various ups and downs in areas of study and issues of Islamic scientific studies that occur.